Utterances in pharmacist-patient communication: A critical discourse analysis - Dewi, Kadek Maya Cyntia (Universitas Jambi, Indonesia, 2026)
Effective communication between pharmacists and patients is essential for ensuring medication adherence, health literacy, and patient satisfaction. As pharmacists increasingly assume educational and counseling roles, the quality of their interaction with patients becomes a crucial determinant of healthcare outcomes. This study employs Critical Discourse Analysis (CDA) to examine utterance patterns and power relations in pharmacist–patient consultations within a community pharmacy setting. Using Fairclough’s three-dimensional framework, the study analyzes three recorded consultations, focusing on terminology, questioning strategies, and expressions of authority. The findings reveal that pharmacists frequently use medical terminology and directive language, which may unintentionally reinforce hierarchical power structures and limit patient participation. Closed-ended questioning patterns further limit patient engagement, while patients often show linguistic deference toward to pharmacists’ authority. The findings provide empirical evidence for integrating discourse awareness and patient-centered communication strategies into pharmacy education curricula. Strengthening pharmacists’ communicative competence may foster collaborative relationships and improve health outcomes.